Peran Manajemen Waktu dan Leader-Member Exchange terhadap Kinerja Pegawai Negeri Sipil - Ilma Iftahul Ula; Fendy Suhariadi (Jurnal Psikologi Teori dan Terapan, 2019)
The performance of civil servants is important to be measured by each regional government in Indonesia. Thus, the Regional Government in District X in East Java has been renewing the performance appraisal method for civil servants in its educational unit by using the e-performance application. The e-performance is used to monitor the suitability of the working hours of each civil servant. The successful use of e-performance will be determined by the role of supervisors. Based on this fact, this study examined the influence of time management and leader-member exchange on the performance of civil servants in District X through the implementation of e-performance system. Hypothesizes of this study were tested using multiple regression analysis. Data were collected using time management and leader-member exchange scales. A total of 285 civil servants in District X which consist of 38.6% men and 61.4% women were involved in this study. The results show that there is positive effect of time management and leader-member exchange on the performance of participants. This study concludes that a positive time management and leader-member exchange among participants will lead to their better performances.  Keywords: Time management, leader-member exchange, civil servants, performance